Canva-Based Animated Video Development for Enhancing EFL Listening Instruction in Junior High School - Karlina Julyanty; Sri Supiah Cahyati; Yana (PROJECT (Professional Journal of English Education), 2026)
This study aimed to describe the process of developing Canva-driven animated videos for EFL listening instruction for the seventh-grade students and to examine the feasibility of the media as well as students’ responses to its use. This study employed a Research and Development (R&D) approach based on the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The participants were 33 seventh-grade students from one of the Islamic junior high school  in Cimahi. The data were collected through observation sheet, validation, and a closed-ended students responses questionnaire consisting 10 item measured on a four-poin likert scale. The developed product focused on the topic “Greetings and leave taking” and was presented in the form of an animated video. The observation results indicated that students needed more engaging instructional media to support listening instruction. The feasibility of the media was evaluated by two expert validator, and the validation result showed that the developed animated video was categorized as good to very good in terms of content appropriateness, alignment with learning objectives, audio-visual quality, and overall attractiveness, indicating that the media is suitable for use. Ultimately, the results showed that students responded favorably to the animated video learning materials, with an average score of 90% (Highly positive). These findings indicate that animated videos have the potential to enhance students’ motivation, engagement, and listening comprehension.